Peran Adopsi Teknologi Informasi dalam Memediasi Hubungan Kemampuan Akuntansi Terhadap Keberlanjutan UMKM di Jawa Tengah - Salecha, Aulia Hafitd; ., Winarsih (EconBank: Journal of Economics and Banking, 2024)
Sustainability of MSMEs must be carried out by every business actor, the existence of very tight competition requires MSME players to develop their business. This research will examine the factors that support the sustainability of MSMEs, in this case namely accounting capabilities with the adoption of information technology as an intervening variable. The aim of this research is to provide an understanding of the use of accounting which is very important for MSMEs, supported by the use of information technology which will make it easier for business actors to obtain information to manage their business. The research method used is a quantitative method and the respondents for this research were 400 Micro, Small and Medium Enterprises in the Central Java region. The sample collection technique uses the non-prurposive sampling method by dividing questionnaires. Keywords: Accounting capabilities, SMEs, Sustainability, Information Technology Adoption, Accounting